Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To solve the equation [tex]\((4x - 16)^{\frac{1}{2}} = 36\)[/tex], we need to go through the following steps:
1. Square both sides of the equation to eliminate the square root:
[tex]\[ \left( (4x - 16)^{\frac{1}{2}} \right)^2 = 36^2 \][/tex]
This simplifies to:
[tex]\[ 4x - 16 = 1296 \][/tex]
2. Isolate the term involving [tex]\(x\)[/tex]:
To do this, add 16 to both sides of the equation:
[tex]\[ 4x - 16 + 16 = 1296 + 16 \][/tex]
Which simplifies to:
[tex]\[ 4x = 1312 \][/tex]
3. Solve for [tex]\(x\)[/tex]:
Divide both sides by 4:
[tex]\[ x = \frac{1312}{4} \][/tex]
Simplifying the division:
[tex]\[ x = 328 \][/tex]
4. Verify the solution:
Substitute [tex]\(x = 328\)[/tex] back into the original equation to ensure both sides are equal:
[tex]\[ (4 \cdot 328 - 16)^{\frac{1}{2}} = 36 \][/tex]
Simplifying inside the parentheses:
[tex]\[ (1312 - 16)^{\frac{1}{2}} = 36 \][/tex]
Which becomes:
[tex]\[ (1296)^{\frac{1}{2}} = 36 \][/tex]
Since [tex]\(1296\)[/tex] is the square of [tex]\(36\)[/tex] ([tex]\(36^2 = 1296\)[/tex]), taking the square root of [tex]\(1296\)[/tex] indeed gives [tex]\(36\)[/tex]:
[tex]\[ 36 = 36 \][/tex]
Thus, the solution to the equation [tex]\((4x - 16)^{\frac{1}{2}} = 36\)[/tex] is [tex]\(x = 328\)[/tex].
Therefore, the correct answer is:
[tex]\[ x = 328 \][/tex]
1. Square both sides of the equation to eliminate the square root:
[tex]\[ \left( (4x - 16)^{\frac{1}{2}} \right)^2 = 36^2 \][/tex]
This simplifies to:
[tex]\[ 4x - 16 = 1296 \][/tex]
2. Isolate the term involving [tex]\(x\)[/tex]:
To do this, add 16 to both sides of the equation:
[tex]\[ 4x - 16 + 16 = 1296 + 16 \][/tex]
Which simplifies to:
[tex]\[ 4x = 1312 \][/tex]
3. Solve for [tex]\(x\)[/tex]:
Divide both sides by 4:
[tex]\[ x = \frac{1312}{4} \][/tex]
Simplifying the division:
[tex]\[ x = 328 \][/tex]
4. Verify the solution:
Substitute [tex]\(x = 328\)[/tex] back into the original equation to ensure both sides are equal:
[tex]\[ (4 \cdot 328 - 16)^{\frac{1}{2}} = 36 \][/tex]
Simplifying inside the parentheses:
[tex]\[ (1312 - 16)^{\frac{1}{2}} = 36 \][/tex]
Which becomes:
[tex]\[ (1296)^{\frac{1}{2}} = 36 \][/tex]
Since [tex]\(1296\)[/tex] is the square of [tex]\(36\)[/tex] ([tex]\(36^2 = 1296\)[/tex]), taking the square root of [tex]\(1296\)[/tex] indeed gives [tex]\(36\)[/tex]:
[tex]\[ 36 = 36 \][/tex]
Thus, the solution to the equation [tex]\((4x - 16)^{\frac{1}{2}} = 36\)[/tex] is [tex]\(x = 328\)[/tex].
Therefore, the correct answer is:
[tex]\[ x = 328 \][/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.